Analysis of Enterococci populations in Town Run - Biafore, Ava; Reynolds, Sara (Proceedings of the West Virginia Academy of Science, 2025)
Enterococci species are ubiquitous, commensal Gram-positive bacteria that support the metabolic functions of the gut microbiome. However, the natural plasticity of enterococci allows them to adapt under selective pressures, such as antibiotics, and develop multi-drug resistance (MDR). CDC reported evidence suggests MDR enterococci spread between patients through providers or devices in hospitals, causing nosocomial infections. As fecal coliform bacteria, enterococci can be found in surface water alongside other enteric bacteria like E. coli and Salmonella. Shepherdstown, WV is home to a surface water tributary called Town Run, designated as a water source for the public in the event of an emergency (Pearson, 2024). It runs through the town, emptying into the Potomac River. Studies underway are exploring the water quality of Town Run, the abundance of bacteria at various sites and how these factors change over time. In this study, we characterize various enterococci isolated from Town Run to better understand the abundance of antibiotic-resistant enterococci in this community. In brief, enterococci were isolated from Town Run water based on their ability to hydrolyze esculin on Bile Esculin Agar. Isolates were Gram stained to confirm a Gram-positive reaction, ovoid shape and chain arrangement. Additional traits were used to identify species as outlined in Bergey’s Manual of Determinative Bacteriology. Individual isolates were then screened using a Kirby-Bauer antibiotic sensitivity test against ten common antibiotics, including penicillin and kanamycin. Future studies aim to assess resistance to vancomycin and quinolones as well as to determine if any areas of Town Run have a higher abundance of enterococci.